2016
DOI: 10.1093/femsec/fiw250
|View full text |Cite
|
Sign up to set email alerts
|

The Specific and Exclusive Microbiome of the Deep-Sea Bone-Eating Snail, Rubyspira osteovora

Abstract: Rubyspira osteovora is an unusual deep-sea snail from Monterey Canyon, California. This group has only been found on decomposing whales and is thought to use bone as a novel source of nutrition. This study characterized the gut microbiome of R. osteovora, compared to the surrounding environment, as well as to other deep-sea snails with more typical diets. Analysis of 16S rRNA gene sequences revealed that R. osteovora digestive tissues host a much lower bacterial diversity (average Shannon index of 1.9; n = 12)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…This genus has been described in other models including algae and several invertebrates such as oysters (King et al, 2012;Clerissi et al, 2018), abalone (Huang et al, 2010), and sacoglossans (Davis et al, 2013). It has also been described as being one of the most abundant microorganisms in the deep-sea bone-eating snail, Rubyspira osteovora (Aronson et al, 2016). Its role in these organisms remains unclear, but some authors hypothesized that they may help with digestion (Fraune and Zimmer, 2008;Duperron et al, 2012;Aronson et al, 2016), notably because of its presence in the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This genus has been described in other models including algae and several invertebrates such as oysters (King et al, 2012;Clerissi et al, 2018), abalone (Huang et al, 2010), and sacoglossans (Davis et al, 2013). It has also been described as being one of the most abundant microorganisms in the deep-sea bone-eating snail, Rubyspira osteovora (Aronson et al, 2016). Its role in these organisms remains unclear, but some authors hypothesized that they may help with digestion (Fraune and Zimmer, 2008;Duperron et al, 2012;Aronson et al, 2016), notably because of its presence in the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been described as being one of the most abundant microorganisms in the deep-sea bone-eating snail, Rubyspira osteovora (Aronson et al, 2016). Its role in these organisms remains unclear, but some authors hypothesized that they may help with digestion (Fraune and Zimmer, 2008;Duperron et al, 2012;Aronson et al, 2016), notably because of its presence in the digestive tract. In the present study, bacteria belonging to the genus Cloacibacterium have been found in all Biomphalaria strains and species, and C. haliotis has been described in another mollusk, the sea snail Haliotis discus (Hyun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Marine molluscs are one of the most diverse and ecologically important groups of marine invertebrates, with many species providing a variety of ecosystem services including supporting commercial and artisanal fisheries. Information about the diversity and compositions of microbes associated with molluscan hosts still remains scarce, although microbiomes of some bivalve (Prieur et al, 1990;Betcher et al, 2012;King et al, 2012;Lokmer et al, 2016;Pierce et al, 2016;Arfken et al, 2017) and gastropod (Dudek et al, 2014;Zbinden et al, 2014;Aronson et al, 2017;Cicala et al, 2018) species have been quantified. Moreover, existing analyses of marine gastropod microbiomes have primarily focused on the digestive tract, with only one study including gillspecific microbiome data (Zbinden et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the data available for marine molluscs are not sufficient to evaluate the relative roles of geographic location and host identity in structuring the microbiome of a host. While studies focusing on microbiomes of multiple species at a particular site show that host identity plays a major role in determining microbiome composition (Davis et al, 2013;Aronson et al, 2017;Cicala et al, 2018), analyses of bivalves in aquaculture settings have shown that rearing the same host in different locations tends to change the relative abundances of a number of microbial phyla between individuals, which suggests that the external environment can also have a substantial effect on the composition of molluscan microbiomes (Trabal et al, 2012;Trabal Fernández et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…vulnificus; (39)). Along with Vibrio genomes, GFC 49 contained also genomes from additional taxa (e.g., Photobacterium (3 strains) and Psychromonas (2 strains)) which are also potential pathogens or gut endobionts of crustacean and marine snails (42,43).…”
Section: Supplementary Information and Supplementarymentioning
confidence: 99%